(untitled) - Goldblatt, Dr. Joe (Hoboken, N.J., 2013)
Providing a comprehensive guide to understanding, planning, promoting, and producing special events, this seventh edition of Special Events, 7th Edition describes the theory and practice of all aspects of event management. Written for current and future event leaders, the text continues to expand its emphasis on the growing globalization of the profession, taking into account the skills leaders need to deal with other cultures, societies, and business practices to plan and deliver successful events. New coverage includes sustainability, technology, security/risk management, and the impact of social media on events and event marketing. 15 all-new case studies have been included, as well as a brief glossary of terms at the end of each chapter to further define the terms used in the chapter.
Keywords: Special events,Sự kiện đặc biệt; Management,Quản lý